Empresas según organización jurídica y la recaudación tributaria en el Perú periodo 2018 – 2022 - Apagüeño Aspajo, Boris (2025)
Private entrepreneurship is not only the engine of the economy by generating the goods and services required in every society, but it is also the main source of employment and income for workers. This doctoral thesis investigates the relationship between tax collection and the number of companies organized as Natural Persons that are in operation. To this end, the historical value of the behavior of these variables is studied in the five-year period 2018-2022, which makes this research quantitative; however, it is correlational at the same time because it investigates the variables scrutinized are associated. The values are taken identically to those listed in the data sources, so the design is non experimental. The conclusions reached establish that the taxes collected are not associated with the number of companies registered as Natural Persons and operating in the five-year period 2018-2022; since the correlation coefficient was r = -0.075217949; and the Coefficient of Determination was R2 = 0.005657740. Companies organized as Natural Persons predominate in the business stock in Peru (61.71%). The Retail Trade economic activity is the one that concentrates the majority of companies registered as Natural Persons (43.62%). Companies incorporated as Public Limited Companies carry out the Business Services activity (21.12%).